1988
DOI: 10.1148/radiology.166.1.2962224
|View full text |Cite
|
Sign up to set email alerts
|

Blue toe syndrome: treatment with anticoagulants and delayed percutaneous transluminal angioplasty.

Abstract: The spontaneous onset of a painful unilateral blue toe is usually caused by fibrinoplatelet microemboli arising from an upstream stenotic or occlusive lesion of the iliac or femoral artery. This constellation of findings is referred to as the blue toe syndrome (BTS). In 12 patients who experienced 14 spontaneous episodes of BTS, angiography demonstrated 15 proximal atherosclerotic arterial lesions, which were presumed to be the source of the microemboli. Fourteen of the 15 lesions were short-segment stenoses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Therefore, thrombogenic and atherogenic sources of emboli need to be considered in the diagnostic work-up. Establishing the underlying cause of BTS is important since, if untreated, BTS arising from embolization can frequently be complicated by further emboli that not only result in the loss of digits but also the forefoot and limb, sometimes causing death [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, thrombogenic and atherogenic sources of emboli need to be considered in the diagnostic work-up. Establishing the underlying cause of BTS is important since, if untreated, BTS arising from embolization can frequently be complicated by further emboli that not only result in the loss of digits but also the forefoot and limb, sometimes causing death [10].…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 BTS is a well-known entity, mostly affecting the older age group, secondary to plaque breakdown that embolizes to the digital arteries, causing bluish discoloration and sometimes even gangrene of a toe in patients with palpable pedal pulses. 7 Among the younger age groups, hypercoagulability states is the most common cause of this syndrome in healthy individuals, while other causes are related to the primary disease of the affected patient, such as Raynaud's disease, polycystemia vera, or thrombocytosis. "Embolic material" that is not located in bifurcation areas should alert the treating physician to look for an unordinary cause of the embolic phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Anecdotal experience and a few small published series have shown that transluminal angioplasty can sometimes be used to sufficiently treat embolizing lesions. 14,17 The remodeling process that occurs with balloon injury theoretically results in stabilization of the ulcerated atherosclerotic plaque. Stent placement may provide a protective scaffold to help secure these lesions.…”
Section: Discussionmentioning
confidence: 99%